PENGARUH RISIKO OPERASIONAL DAN STRATEGI MITIGASI TERHADAP PRODUKTIVITAS PERUSAHAAN E-COMMERCE PADA SHOPEE INDONESIA - Hadi Mulyono; Arief Syah Safrianto (Jurnal Ekonomi dan Industri, 2026)
This study aims to analyze the influence of operational risk and mitigation strategies on the productivity of e-commerce companies at Shopee Indonesia. This study uses a quantitative approach. The study population was Shopee Indonesia's operational employees, with a sample of 47 respondents selected using a purposive sampling technique. The data analysis method used was multiple and simple linear regression analysis. The results show that operational risk significantly influences the productivity of Shopee Indonesia. In addition, mitigation strategies have been shown to have a positive and significant impact on Shopee Indonesia's productivity.